Statistical observations of the MLT, latitude and size of pulsed ionospheric flows with the CUTLASS Finland radar - G. Provan; T. K. Yeoman (Annales Geophysicae, 1999)
A study has been performed on the occurrence of pulsed ionospheric flows as detected by the CUTLASS Finland HF radar. These flows have been suggested as being created at the ionospheric footprint of newly-reconnected field lines, during episodes of magnetic flux transfer into the terrestrial magnetosphere (flux transfer events or FTEs). Two years of both high-time resolution and normal scan data from the CUTLASS Finland radar have been analysed in order to perform a statistical study of the extent and location of the pulsed ionospheric flows. We note a great similarity between the statistical pattern of the coherent radar observations of pulsed ionospheric flows and the traditional low-altitude satellite identification of the particle signature associated with the cusp/cleft region. However, the coherent scatter radar observations suggest that the merging gap is far wider than that proposed by the Newell and Meng model. The new model for cusp low-altitude particle signatures, proposed by Lockwood and Onsager and Lockwood provides a unified framework to explain the dayside precipitation regimes observed both by the low-altitude satellites and by coherent scatter radar detection. Key words. Magnetospheric physics (magnetosphere · ionosphere interactions; plasma convection; solar wind-magnetosphere interactions)